Marketing Efficiency of Chicken’s Egg in Binjai City, North Sumatra - Kiki Pargita; Armyn Hakim Daulay; Nurzainah Ginting; Yusuf Leonard Henuk; Edhy Mirwandhono (Jurnal Peternakan Integratif, 2018)
The egg marketing by producers usually uses various marketing agencies so that chicken eggs will reach consumers. This process requires marketing costs to be used to perform marketing functions. Therefore, research is conducted to investigate the marketing channels, marketing institutions, marketing functions and investigate the marketing efficiency of chicken’s egg found in Binjai City. This research was conducted from July to August 2018. The method used in data collection is the withdrawal of a sample of retailers using the purposive sampling method, while the sample of farmers and other marketing institutions with snowball sampling. Data collection was done by interview technique using a questionnaire. Data analysis includes marketing costs, marketing margins, farme’r share and cost benefit ratio of each marketing channel. The results of this study indicate that there are two marketing channels. The smallest marketing margin is obtained by the second marketing channel, therefore the second marketing channel has the largest ratio of profit to cost. The biggest farmer's share is obtained in the second marketing channel, this channel only uses retailers as an intermediary channel. So it can be concluded that the second channel is the most efficient channel because it has the smallest cost and the profit is spread evenly across all the marketing institutions that play a role.